2016
DOI: 10.1016/j.ram.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antifungal susceptibility of Candida albicans and its related species Candida dubliniensis and Candida africana isolated from vulvovaginal samples in a hospital of Argentina

Abstract: Candida africana taxonomical status is controversial. It was proposed as a separate species within the Candida albicans species complex; however, phylogenetic analyses suggested that it is an unusual variety of C. albicans. The prevalence of C. albicans-related species (Candida dubliniensis and C. africana) as vulvovaginal pathogens is not known in Argentina. Moreover, data on antifungal susceptibility of isolates causing vulvovaginal candidiasis is scarce. The aims of this study were to establish the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 28 publications
5
25
2
2
Order By: Relevance
“…Consistent with the last phylogenetic evidence [ 17 , 39 ], we found that C. dubliniensis and C. africana fell into C. albicans complex as shown for ITS1-5.8S-ITS2 gene in Figure 3 . The phylogenetic tree of HWP1 gene indicated that the C. dubliniensis isolates formed a monophyletic group nested within the clade of C. albicans .…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the last phylogenetic evidence [ 17 , 39 ], we found that C. dubliniensis and C. africana fell into C. albicans complex as shown for ITS1-5.8S-ITS2 gene in Figure 3 . The phylogenetic tree of HWP1 gene indicated that the C. dubliniensis isolates formed a monophyletic group nested within the clade of C. albicans .…”
Section: Discussionsupporting
confidence: 90%
“…This result corroborates the findings reported in Iran-where the frequency C. africana (3%) and C. dubliniensis (0%) was reported among 100 vaginal isolates of C. albicans species complex [10] –and a multicenter study that reported a higher frequency of C. africana (7.2%) than C. dubliniensis (2.9%), among Candida isolates recovered from 498 clinical specimens originated from various patient groups [26] . However, the higher isolation rate of C. dubliniensis over C. africana is being reported from other studies [9] , [13] , [19] , [20] . Whereas C. dubliniensis is being predominantly recovered from oral and oropharyngeal lesions of HIV/AIDS patients, isolates were shown to be recovered from other patients suffering from cancer [14] , cystic fibrosis [27] , genital and respiratory tracts infections [9] – [13] , [19] , [20] , [28] , and from a gastric fluid sample [26] .…”
Section: Discussionmentioning
confidence: 80%
“…However, the higher isolation rate of C. dubliniensis over C. africana is being reported from other studies [9] , [13] , [19] , [20] . Whereas C. dubliniensis is being predominantly recovered from oral and oropharyngeal lesions of HIV/AIDS patients, isolates were shown to be recovered from other patients suffering from cancer [14] , cystic fibrosis [27] , genital and respiratory tracts infections [9] – [13] , [19] , [20] , [28] , and from a gastric fluid sample [26] . The reason(s) for the disparate frequencies of isolation might be linked to factors such as the difference in the quality of sampling, the anatomic sites, the nature of the clinical sample, the underlying disease entities, racial or genotypic differences, and the immune status of the individuals involved.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, currently C. africana is known as a biovariant of C. albicans with an exceptional capacity to colonize human genitalia and cause mainly vaginal infections (Romeo and Criseo, 2011; Romeo et al, 2013). Its distribution appears to be worldwide, with cases of infection reported from China (Shan et al, 2014; Hu et al, 2015), Japan (Odds et al, 2007), South Korea (Song et al, 2014), Colombia (Rodríguez-Leguizamón et al, 2015), Argentina (Theill et al, 2016), Chile (Odds et al, 2007), India (Sharma et al, 2014), Iran (Yazdanparast et al, 2015), Africa (Tietz et al, 2001; Dieng et al, 2012; Nnadi et al, 2012; Ngouana et al, 2015), USA (Romeo et al, 2013), and Europe (Alonso-Vargas et al, 2008; Romeo and Criseo, 2009; Borman et al, 2013). However, despite the efforts made so far, it is rather difficult to discriminate C. africana from C. albicans in clinical diagnostic laboratories and therefore its epidemiology is still unclear and needs more investigation (Romeo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%